Probiotics and Oral Health - -, Prathap; Prathap, Shruthy (Journal of Orofacial Research, 2011)
Probiotics utilize naturally occurring bacteria to confer a health benefits when administered in adequate amounts. A few conventional foods containing probiotics are yogurt, fermented and unfermented milk, soya beverages etc. Most often , they come from two groups of bacteria, Lactobacillus or Bifidobacterium. Probiotics have been extensively studied for their health promoting effects. Scientific understanding of probiotics and their potential for preventing and treating oral diseases is at its infancy. This review is focused on the use of probiotics as preventive and therapeutic products for oral healthcare.